2017
DOI: 10.1016/j.drugalcdep.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site exploration of sex differences in brain reactivity to smoking cues: Consensus across sites and methodologies

Abstract: Background Biological sex influences cigarette smoking behavior. More men than women smoke, but women have a harder time quitting. Sex differences in smoking cue (SC) reactivity may underlie such behavioral differences. However, the influence of sex on brain reactivity to SCs has yielded inconsistent findings suggesting the need for continued study. Here, we investigated the effect of sex on SC reactivity across two sites using different imaging modalities and SC stimulus types. Methods Pseudo-continuous art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“…The current study, however, suggests that female problem drinkers, on a neural level, are insensitive to alcoholrelated cues, despite similar levels in alcohol use severity, which is in line with the findings of one earlier EEG study in alcohol use disorder (Petit et al, 2013). Moreover, the current findings are also in line with several neural cue-reactivity studies in nicotine dependence (Cosgrove et al, 2014;Dumais et al, 2017). Animal studies have also reported that acute and chronic alcohol exposure only alters striatal mRNA expression in male, but not in female rats (Baxter-Potter et al, 2017) and that there is a differential involvement of serotonergic and noradrenergic signalling in cue-induced reinstatement (Kohtz & Aston-Jones, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study, however, suggests that female problem drinkers, on a neural level, are insensitive to alcoholrelated cues, despite similar levels in alcohol use severity, which is in line with the findings of one earlier EEG study in alcohol use disorder (Petit et al, 2013). Moreover, the current findings are also in line with several neural cue-reactivity studies in nicotine dependence (Cosgrove et al, 2014;Dumais et al, 2017). Animal studies have also reported that acute and chronic alcohol exposure only alters striatal mRNA expression in male, but not in female rats (Baxter-Potter et al, 2017) and that there is a differential involvement of serotonergic and noradrenergic signalling in cue-induced reinstatement (Kohtz & Aston-Jones, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Altogether, these few studies suggest that alcohol cues induce craving and neural cue‐reactivity in men only, which may be related to a differential role of negative effect. Moreover, while sex differences in anterior cingulate cortex (ACC) cue‐reactivity have not been reported in alcohol drinkers, cue‐reactivity studies in other substance use disorders have reported less ACC cue‐reactivity in female, compared to male, cocaine users (Volkow et al., ) and smokers (Dumais et al., ). However, also greater ACC cue‐reactivity has been found in female, compared to male, cocaine users (Kilts, Gross, & Ely, ) and smokers (Zanchi, Brody, Borgwardt, & Haller, ), whereas some studies did not find any sex differences in ACC cue‐reactivity (Wetherill et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether dACC-AI coupling strength changes along with a reduction in ADHD symptoms in those receiving effective treatment may provide a more causal link. The limited sample size also restricts our ability to identify the interaction of our main variables with other pertinent biological variables such as sex, which is relevant given sex differences in nicotine dependence (Dumais et al, 2017; Wetherill, et al, 2016). Despite these limitations, our work not only supports prior findings that ADHD symptoms contribute to nicotine dependence, but this work strengthens the idea of SN involvement in nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cue-induced brain activity have also shown mixed results for sex differences. Greater activation has been demonstrated in women after exposure to alcohol cues (9) and cocaine cues (13), but men have also shown more activity relative to women in response to cues related to alcohol (8) and cigarettes (14) as well as stress-related cues (9). Variations in experimental design, including types of cues, how they are presented, and the level of current substance use among participants may contribute to some conflicting findings.…”
Section: Introductionmentioning
confidence: 99%